Uniform onset of the long proton bunch self-modulation seeded by an electron bunch in an overdense plasma - K. Moon; E. S. Yoon; M. Chung; P. Muggli; M. Moreira; M. A. Baistrukov (Physical Review Accelerators and Beams, 2023)
The phase, growth rate, and onset of long proton bunch self-modulation in plasma can be controlled by a preceding short charged particle bunch. In this paper, by analyzing the growth rates of the self-modulation obtained from particle-in-cell simulation results, we identify two modes of self-modulation, namely noise-seeded and externally seeded self-modulations, and investigate their onset timings. We find that a uniform onset of the self-modulation at each slice of the long proton bunch is crucial for fine-tuning its phase and amplitude. We then demonstrate that a low-energy and low-current electron seed bunch in overdense plasma generates near-axis radial wakefields similar to those observed in the blowout regime. Consequently, the resultant self-modulation is excited as a single mode simultaneously along the entire long proton bunch.